The effect of state pension cut legislation on bank values - Lee Cohen; Marcia Millon Cornett; Hamid Mehran; Hassan Tehranian (Federal Reserve Bank of New York, 2014)
This study provides an empirical analysis of the impact of Wisconsin and Ohio pension cut legislation on values of banks operating in Wisconsin and Ohio, banks operating in other states in which pension cut legislation was being considered as Wisconsin and Ohio went through its legislative process, and all publicly traded U.S. banks. We find that banks doing business in Wisconsin and Ohio experience positive (negative) stock price reactions to announcements that indicate an increased (a decreased) probability of pension cut legislation. The stock price reactions are positively related to the extent to which banks operate in Wisconsin and Ohio. Stock price reactions are rarely evident for banks in the other thirteen states that were considering pension cut legislation during the period of analysis. We also find municipal bond spreads tighten and bank credit supply increases with pension cut legislation. Overall, the findings suggest states' budget cuts affect bank values and credit supply through their municipal bond holdings.
Keywords: G11; G21; H72; H75; 330; financial institutions; municipal debt; public pensions